Endoscopic vacuum therapy for esophageal perforation: a multicenter retrospective cohort study - Luttikhold, Joanna; Pattynama, Lisanne M. D.; Seewald, Stefan; Groth, Stefan; Morell, Bernhard K.; Gutschow, Christian A.; Ida, Satoshi; Nilsson, Magnus; Eshuis, Wietse J.; Pouw, Roos E. (Endoscopy, 2023)
Background Endoscopic vacuum therapy (EVT) is a novel treatment for esophageal perforations. This study aimed to describe initial experience with EVT of esophageal perforations due to iatrogenic cause, Boerhaave syndrome, or other perforations not related to prior upper gastrointestinal surgery.Methods Data from patients treated with EVT for esophageal perforation at five hospitals in three European countries, between January 2018 and October 2021, were retrospectively collected. The primary end point was successful defect closure by EVT, with or without the use of other endoscopic treatment modalities. Secondary end points included mortality and adverse events.Results 27 patients were included (median age 71 years). The success rate was 89 % (24/27, 95 %CI 77–100). EVT failed in three patients: two deceased during EVT (septic embolic stroke, pulmonary embolism) and one underwent esophagectomy due to a persisting defect. Two adverse events occurred: one iatrogenic defect expansion during sponge exchange and one hemorrhage during sponge removal. Median treatment duration was 12 days (interquartile range [IQR] 6–16) with 1 sponge exchange (IQR 1–3).Conclusion EVT is a promising organ-preserving treatment for esophageal perforations, with a success rate of 89 %. More experience with the technique and indications will likely improve success rates.